A review on modelling ground vibrations generated by underground trains. Issue 4 (2nd October 2019) - Sheng, Xiaozhen
ABSTRACT: With the rapid development of underground railways in urban areas, ground-borne vibrations caused by underground trains have become a great concern in the environmental and transportation communities. Predictions of dynamic responses of a tunnel-soil system to running trains are now commonly practised in environmental vibration evaluation and tunnel serviceability assessment, since the prediction can make clear mechanisms involved, reveal and quantify key factors and help design control measures. In this paper, a review is given to existing methodologies which have been developed for modelling ground vibrations generated by underground trains, together with discussion on issues which are required to be further addressed.